2012
DOI: 10.1117/12.916387
|View full text |Cite
|
Sign up to set email alerts
|

Phase defect printability analyses: dependence of defect type and EUV exposure condition

Abstract: Phase defect printability and imaging characteristics were investigated by using aerial image simulation to clarify the phase defect impact on patterns depending on defect types, and on exposure conditions. In particular, the difference between the impacts caused by the same size bump phase defect and pit phase defect on 28 nm ~ 16 nm L&S projected patterns were investigated by calculating line width variations. Aerial images of phase defects in an absence of any absorber pattern were also calculated, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The distribution of the diffraction signals for the current mask blank fluctuates for defects of 30 nm width and 1 nm depth. Terasawa et al 30) reported that this size of defect causes an 8% line-width error for a 22 nm line-and-space pattern with the scanner that has a NA of 0.33. The deposition process should be optimized to decrease the intensity of scattering from the multilayer.…”
Section: Fluctuations Of the Scattering Distribution At 30-nmwide Def...mentioning
confidence: 99%
“…The distribution of the diffraction signals for the current mask blank fluctuates for defects of 30 nm width and 1 nm depth. Terasawa et al 30) reported that this size of defect causes an 8% line-width error for a 22 nm line-and-space pattern with the scanner that has a NA of 0.33. The deposition process should be optimized to decrease the intensity of scattering from the multilayer.…”
Section: Fluctuations Of the Scattering Distribution At 30-nmwide Def...mentioning
confidence: 99%
“…To evaluate inspection tool sensitivity, PDM is improtant 7 . Influence of phase defect to wafer print has studied 8 . Requested pattern size for seed defect is severe.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, image simulation study has been extensively conducted in order to clarify such phase defect impacts. [19][20][21] Exposure test using EUVL mask with programmed phase defects is an effective way to understand the influence of phase defects on printed patterns, [22][23][24] and to define the specifications of phase defect inspection tool. However, because of the limited capability of current exposure tools for printing 16 nm and sub-16 nm it is difficult to evaluate the impact of phase defect on printed patterns on wafer at these small feature sizes.…”
Section: Introductionmentioning
confidence: 99%